IMPROVING THE GAME WITH A FAST BREAKTHROUGH BASKETBALL PLAYERS OF 15–16 YEARS - Анвар Равилевич Яруллин; Галина Рауфовна Данилова (Физическая культура. Спорт. Туризм. Двигательная рекреация, 2020)
The article tells about one of the most popular tactical interactions are the fast break system. It has many options, but the goal of all of them is the same — the ball must be delivered under the opponent’s ring before the defense has time to organize. The author considers that a quick breakthrough is a well-designed and organized attack system. An attack can start from any place on the court, but very often the attack option depends on the place where a quick breakout starts. As a rule, long or short transmission, guidance or a combination of these techniques are used. The better a team is prepared, the better it will be able to identify and use attack methods.